Perceived Risk of Users Intention to Use Cryptocurrency in Malaysia: A Multi-analytic Approach - Al-amri R.; Al-shami S.; Alkawsi G. (Springer Science and Business Media Deutschland GmbH, 2024)
Cryptocurrency, as the primary successful implementation of blockchain technology, has revolutionized the financial industry. These decentralized digital currencies operate without a central authority, enabling users to conduct independent and efficient transactions for goods and services. By leveraging blockchain platforms, cryptocurrencies confirm the security and legitimacy of these transactions while keeping fees low. Despite its potential, the global acceptance of cryptocurrencies, including Malaysia, has not reached desired levels. This can be attributed to consumer concerns regarding perceived ease of use, perceived usefulness, social influence, and perceived risk. Considering these factors, this research aims to investigate the users perceptions of accepting cryptocurrency applications from a risk perspective. The research utilises the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Perceived Risk Theory to establish and evaluate various hypotheses. The study involved a sample size of 496 individuals. The proposed model is validated via Structural Equation Modelling (SEM), and the data is utilised as inputs for an Artificial Neural Network (ANN) model to predict perceived risk factors. The outcomes show that Performance Expectancy, Effort Expectancy, Social Influence, Financial Risk, and Psychological Risk significantly influence the users behavioral intention to use cryptocurrency in Malaysia from a risk perspective. The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.